Assessment of renal functions in patients of chronic liver disease. (21st October 2015) - Aggarwal, H. K.; Jain, Deepak; Singla, Suhas; Jain, Promil
Abstract: Aims and objectives : Renal involvement in patients of chronic liver disease (CLD) is one of the dreaded complications associated with a steep rise in mortality and morbidity. Derangements in various homeostatic mechanisms in CLD leading to direct renal injury or circulatory compromise have been associated with renal impairment. Method : Consecutive cirrhotic patients ( n  = 100) were included in the study. Structural and functional renal failure was identified and patients were classified into various renal syndromes pre renal, intra-renal and hepatorenal syndrome (HRS). Results : At the time of presentation, 37 patients had renal dysfunction. Thirty patients had pre-renal type of renal failure, six patients had intrinsic renal disease and one patient had structural renal disease. Patients with pre-renal type were further classified into volume responsive pre-renal failure and volume non responsive HRS. Five patients had features suggestive of HRS. Patients with decompensation such as portal hypertension (PHTN), jaundice, upper gastro-intestinal bleed and hepatic encephalopathy had significantly higher incidence of renal derangements as compared to their counterparts. Infection in the form of SBP and/or sepsis predisposed patients to develop renal dysfunction. Conclusion : Renal impairment in patients with advanced liver disease is not an uncommon phenomenon and is more commonly associated with a more advanced disease. Presence of PHTN and various signs of decompensation increase the chances of renal derangements in these patients. In view of rising incidence of CLD and higher survival (due to better treatment options available), one should be vigilant for the renal derangements in these patients.